Perkembangan Konsep Regionalisme Kritis Kenneth Frampton (1985-2005) - Dimas Wihardyanto; . Sherlia (Universitas Bandar Lampung (UBL), 2011)
This paper outlines the development of Critical Regionalism Concept, introduced by Kenneth Frampton, whom a professor in history and architecture. His most influential achievement was a book titled